'Smart building' technology network analysis: applying core–periphery structure analysis. Issue 1 (2nd January 2017) - Madani, Farshad; Daim, Tugrul; Weng, Calvin
Abstract: In this research, network analysis is applied to examine smart building patents to find the most effective technologies and novel opportunities for innovation. Core–periphery structure is the main analysis method deployed to exploit the most effective patents in the core network as basic inventions in smart building technologies, and also to explore the periphery network for novel opportunities to develop new technologies.